Perbandingan Motivasi Belajar dan Kemandirian Belajar Siswa Pengguna dan Bukan Pengguna Bimbel Online (Ruang Guru) SMA Adabiah 1 Padang - Hidayatul Ummah; Rani Sofya (Universitas Negeri Padang, 2023)
This aim of research is to find out 1) Comparison student motivation learning of users and non-users of Ruang Guru online tutoring and 2) Comparison of learning independence of users and non-users of Ruang Guru online tutoring. The population in the research was the XIIth Grade students of Senior High School of Adabiah 1 Padang, as many as 195 students. This research type was comparative descriptive research. The technique of sampling used in the research was purposive sampling. The data used were secondary and primary. Data techniques of collection were in the form of a questionnaire. Data analysis used descriptive analysis, requirements analysis test, and the hypothesis used the Z test used the Independent Sample T-Test, where the analysis was carried out using SPSS 22. The results showed that 1) There was a difference in student motivation between users and non-users of online tutoring in the Ruang Guru, which was significant, as seen from sig 2 tailed 0.001 <0.05. 2) There was a difference between students' learning independence between users and non-users of online tutoring of Ruang Guru had a significant difference. It can be seen from sig 2 tailed 0.000 <0.05.